"Attention Everyone, Time Out!": Safety Attitudes and Checklist Practices in Anesthesiology in Germany. A Cross-Sectional Study. Issue 6 (September 2021) - Neuhaus, Christopher; Spies, Aline; Wilk, Henryk; Weigand, Markus A.; Lichtenstern, Christoph
Abstract : Background: The use of perioperative checklists has generated a growing body of evidence pointing toward reduction of mortality and morbidity, improved compliance with guidelines, reduction of adverse events, and improvements in human factor–related areas. Usual quality management metrics generally fall short in assessing compliance with their perioperative application. Our study assessed application attitudes and compliance with safety measures centered around the World Health Organization (WHO) "Safe Surgery Saves Lives" campaign as perceived by anesthesia professionals in Germany. Methods: Three hundred sixteen physicians and nurses participated in our cross-sectional survey, and 304 completed all 35 questions. Results: Only 59.5% of participants had knowledge of the theoretical framework behind the WHO campaign. During the "sign-in, " patient ID and surgical site were checked in 99.6% and 95.1% as recommended by the WHO. Allergies were addressed by 89.2%, expected difficult airway by 65.7%, and the availability of blood products by 70.5%. A total of 84.9% of participants advocated for the time-out to include all persons present in the operating room, which was the case in 57.0%. A total of 40.8% stated that the time-out was only performed between anesthetist and surgeon; in 17.0% of cases, the patient was simultaneously draped and/or surgically scrubbed. No significant differences between hospital types were observed. Conclusions: Our study paints a heterogeneous picture of the implementation, usage, and safety attitudes concerning the Safe Surgery Checklist as promoted by the WHO. The lack of standardized execution and team-mindedness can be taken as further evidence for the importance of interdisciplinary training focusing on human factors, communication, and collaboration rather than the mere implementation by decree. Abstract : Supplemental digital content is available in the text.